2016
DOI: 10.1248/bpb.b15-01034
|View full text |Cite
|
Sign up to set email alerts
|

Early Therapeutic Intervention for Crush Syndrome: Characterization of Intramuscular Administration of Dexamethasone by Pharmacokinetic and Biochemical Parameters in Rats

Abstract: Crush syndrome (CS) is the systemic manifestation of muscle cell damage resulting from pressure and crushing. It is associated with a high mortality rate, even when patients are treated with conventional therapy. We demonstrated the utility of intramuscular administration of dexamethasone (DEX) in disaster medical care by using a model of CS to characterize the pharmacokinetics and biochemical parameters. We compared intravenous (IV) and intramuscular (IM) injection. The IM sites were the right anterior limb (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Some experiments used a press exerting a force of 100 kg per kg of animal body weight (100:1). In a series studies of tourniquet-induced CS models by the Murata research group, the survival rates of rats in the CS group were nearly 91%, 82%, 36%, 13%, and 13% at 1, 3, 6, 24, and 48 h after reperfusion, respectively (24), which were consistent with the results of the same teams other investigations since 2012 (49–53).…”
Section: Types Of Animals Used In Cs Researchsupporting
confidence: 84%
“…Some experiments used a press exerting a force of 100 kg per kg of animal body weight (100:1). In a series studies of tourniquet-induced CS models by the Murata research group, the survival rates of rats in the CS group were nearly 91%, 82%, 36%, 13%, and 13% at 1, 3, 6, 24, and 48 h after reperfusion, respectively (24), which were consistent with the results of the same teams other investigations since 2012 (49–53).…”
Section: Types Of Animals Used In Cs Researchsupporting
confidence: 84%
“…CS rats displayed characteristic PK of impaired drug metabolism (i.e., inhibition of liver drug-metabolizing enzymes and the formation of the third space) [ 33 ], but we conclude that the high blood concentration of AS (Additional file 13 : Fig. S4) occurred because AS was not renally excreted in CS rats [renal clearance (CL r )/CL tot ratio: 0.159 ± 0.018/0.180 ± 0.012, as measured by HPLC].…”
Section: Discussionmentioning
confidence: 99%
“…Since the CS involves excessive inflammation in the body, researchers have tried to use DXM to treat CS rat models. Murata et al [24][25][26] found that high-dose DXM injections exerted antiinflammatory effects and reduced ischemia/reperfusion injury (IRI) through the PI3K-Akt-eNOS signaling pathway. This significantly improved the early survival rate of CS rat model.…”
Section: Dexamethasonementioning
confidence: 99%
“…Murata et al. [ 24–26 ] found that high-dose DXM injections exerted anti-inflammatory effects and reduced ischemia/reperfusion injury (IRI) through the PI3K-Akt-eNOS signaling pathway. This significantly improved the early survival rate of CS rat model.…”
Section: Chemical Drugsmentioning
confidence: 99%